Nilai-Nilai Pendidikan Islam Dalam Tradisi Kelahiran Pada Adat Banjar - Shapiah, Shapiah (IAIN Antasari Banjarmasin, 2015)
Islam, Banjarese, is a religious identity that cannot be separated from their identities. The symbolic manifestations of their religiousity appear in the form of religious ceremonies associated with the life cycle, such as marriage, giving birth, and death. One important phase of life for the people of Banjar is the birth phase. The birth of a baby has a sacred meaning in the social life of Banjar. The presence of a baby in the family is often called for a special ceremony or ritual which is loaded with belief and religious symbols and values. The study has identified that all the cultural procession which surrounds the birth of an individual contain many educational values of Islam. This is evident in several stages through the birth phase in the tradition of Banjar, such as mandi badudus, batasmiyah/aqiqah, batindik, baayun, and bakhitan